Relationship between risk behaviors for eating disorders and maturational process in young athletes - Leonardo de Sousa Fortes; Maria Aparecida Conti; Maria Elisa Caputo Ferreira (Revista Brasileira de Atividade Física e Saúde)
The aim of the study was to analyze the relationship between risk behavior for eating disorders (ED) and maturational process, according to sex. 580 athletes, of both genders, aged between 10 and 19 years participated of the study. ED was assessed by the Eating Attitudes Test (EAT-26). We applied the Body Shape Questionnaire (BSQ) to assess body dissatisfaction. Sitting-height, height and weight were measured to estimate the age of somatic maturation. Sexual maturation was assessed by the criteria of “Tanner”. Results showed prevalence of 18,1 and 14,7% of behavior for ED in girls and boys, respectively. There was no difference in the EAT-26 scores as a function of maturational stages, but this score was associated with maturational stages in males (p